Dropout among students in higher education: a case study - Garrido Silva, Claudia Angelica; Pajuelo Diaz, Jacqueline (Universidad Ciencia y Tecnología, 2023)
It is known as a university dropout when a student, for various reasons, abandons his academic training and moves away from the educational system. This problem is very present worldwide, directly affecting the education of many young people and requiring specialists and professionals to find a solution. In this work, the factors that influence university dropout were analyzed according to the perception of students of the faculty of education of the Universidad Nacional Mayor de San Marcos (UNMSM) during the year 2019, for which a questionnaire of 30 items was applied. Given the results obtained, it is possible to affirm that the most influential factors are personal, academic, economic, and institutional. In addition, it was concluded that university dropout is a problem of great complexity that encompasses a wide range of factors that influence a student’s academic life in different ways.